2014
DOI: 10.1063/1.4901026
|View full text |Cite
|
Sign up to set email alerts
|

Thin silicon foils produced by epoxy-induced spalling of silicon for high efficiency solar cells

Abstract: We report on the drastic improvement of the quality of thin silicon foils produced by epoxy-induced spalling. In the past, researchers have proposed to fabricate silicon foils by spalling silicon substrates with different stress-inducing materials to manufacture thin silicon solar cells. However, the reported values of effective minority carrier lifetime of the fabricated foils remained always limited to ∼100 μs or below. In this work, we investigate epoxy-induced exfoliated foils by electron spin resonance to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Characterization of the fractured surface of the as-exfoliated Si via electron spin resonance (ESR) and photoluminescence (PL) imaging shows that the defects cause significant reduction in the minority carrier lifetime. 28 The defects at the fracture surface can be appropriately removed by etching away a few micrometers of Si from the fracture surface via a wet-etching process. 64 Another approach to fabricate cost-effective heterojunction solar cells is through the utilization of 2D materials.…”
Section: Crack-assisted Layer Transfer With Interfacial Fracture Toug...mentioning
confidence: 99%
See 2 more Smart Citations
“…Characterization of the fractured surface of the as-exfoliated Si via electron spin resonance (ESR) and photoluminescence (PL) imaging shows that the defects cause significant reduction in the minority carrier lifetime. 28 The defects at the fracture surface can be appropriately removed by etching away a few micrometers of Si from the fracture surface via a wet-etching process. 64 Another approach to fabricate cost-effective heterojunction solar cells is through the utilization of 2D materials.…”
Section: Crack-assisted Layer Transfer With Interfacial Fracture Toug...mentioning
confidence: 99%
“…To avoid the above-mentioned disadvantages, a thermosetting polymer based thin film can be used as a stressor layer. The polymer layer can be easily deposited by drop-casting or spin coating on a target substrate. In addition, the large difference in thermal expansion coefficients of the polymer layer and the semiconductor allows a significant reduction in the annealing temperature to below 150 °C to induce sufficient thermal misfit stress for crack growth.…”
Section: Working Principles Of the Crack-assisted Layer Transfer Tech...mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Martini et al reached minority carrier lifetimes of 461 ls on a 100 lm thick foil of 1 X cm n-type material. 17 Measuring quasi-steady-state photoconductance (QSSPC) 18 on freestanding exfoliated silicon films, Saha et al found no degradation of the bulk carrier lifetime compared to the parent substrate before lift-off and showed a solar cell produced from a 25 lm thick exfoliated SOM silicon layer with nickel rear contact and an efficiency of 14.9% on a small area. 19 These results are encouraging for using spalled layers as solar cell absorber materials.…”
Section: Introductionmentioning
confidence: 99%
“…17,21 Within this paper, we present exfoliated silicon foils that were produced using an evaporated Al film as stressor layer. The use of a metal shows a distinct advantage for photovoltaic applications: To reduce the wafering costs it is preferable not to remove the stressor layer after lift-off but to use it as a functional layer.…”
Section: Introductionmentioning
confidence: 99%